Happiness: In Psychological and Islamic Aspects - Rajabov, Elvin (Scholarya Demo Journal of Ruby, 2020)
The subject of happiness has always been of interest to philosophers, psychologists and experts in various fields. For this reason, research has been conducted on various aspects of this topic and various theories have been put forward. Considering different aspects, psychologists involved in the study of human happiness mention various approaches based on their observations and experiments. There is also a special approach to happiness in the Islamic aspect, as human happiness is of great importance. This article first discusses the different approaches that psychologists have to the subject of happiness. Later, the subject of happiness in the Islamic aspect was studied. The first part of the article discusses the different approaches of psychologists to the topic of happiness. Among these approaches, the approaches of Martin Seligman and Mihaly Csikszentmihalyi, representatives of Positive Psychology, who focus on human happiness, were mentioned. The approach of psychoanalysis to happiness, which has a special approach in the field of psychology, has also been studied. Then there is information about the Eudemonist approach, which is the approach of the representatives of the current of humanistic psychology. Theories of cognitive and behavioral psychology related to happiness are also discussed. The second part of the article explores the topic of happiness in the Islamic aspect. This section focuses on the subject of happiness in Islamic sources. The concepts used in the Holy Qur'an related to the subject of happiness are mentioned. Then the importance of meeting one's spiritual and physical needs for happiness was discussed. Also, the ways of living a happy life in the Islamic aspect and the activities and behaviors mentioned for happiness have been studied. The importance of man's constant remembrance of God as a source of lasting happiness has been emphasized.